A carbon nanotube and its preparation method

By using highly dispersed transition metal catalysts in the preparation of carbon nanotubes, the pyrolysis reaction and catalytic modification reaction of waste plastics are coupled in one reactor, solving the problems of complex processes and high costs in the prior art, and achieving a step of preparing easy-to-functional carbon nanotubes, with a simple process and low cost.

CN116553528BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210103846.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-28
Publication Date
2025-04-01
Estimated Expiration
2042-01-28

AI Technical Summary

Technical Problem

The existing carbon nanotube preparation methods have problems such as long process routes, complex catalyst preparation, high production costs, complex process routes, and difficult microwave power regulation.

Method used

By preparing a highly dispersed transition metal catalyst, the pyrolysis reaction of waste plastic and the catalytic modification reaction are coupled in a reactor, and easy-to-functional carbon nanotubes are prepared by a one-step pyrolysis reaction.

Benefits of technology

It realizes the preparation of carbon nanotubes with simple processes, simple operations and low cost. The prepared carbon nanotubes are graphitized and easily oxidized within a reasonable range, and are easy to chemically modify and modify, which broadens their application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116553528B_ABST
    Figure CN116553528B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon nanotube and a preparation method thereof, wherein the functionalization index α of the carbon nanotube is 0.4 to 0.6; the preparation method of the carbon nanotube comprises the following steps: (1) petroleum coke, a transition metal precursor, a support precursor and an activator are uniformly mixed and then activated, and then washed and dried to obtain a sample A; (2) in the presence of an oxygen-containing atmosphere, the sample A obtained in step (1) is treated to obtain a sample B after the treatment; (3) under contact conditions, the sample B obtained in step (2) is uniformly mixed with waste plastics and subjected to a pyrolysis reaction to obtain carbon nanotubes after the reaction. The present invention prepares a highly dispersed transition metal catalyst, couples the pyrolysis reaction and the catalytic modification reaction of the waste plastics in a reactor, and can prepare easily functionalized carbon nanotubes through a one-step pyrolysis reaction, which has the advantages of simple process and operation and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon material preparation, and in particular relates to a carbon nanotube and a preparation method thereof. Background Art

[0002] In 1991, Japan's NEC Corporation first discovered carbon nanotubes, which has since opened people's attention to carbon nanotubes. Due to its unique structure and mechanical and electrical properties, carbon nanotubes have broad application potential in nanoelectronic devices, catalyst carriers, energy storage materials, super-strong composite materials and other fields. Currently, common carbon nanotube synthesis methods include arc discharge, laser ablation, chemical vapor deposition and flame pyrolysis. Among them, arc discharge and laser ablation both have harsh reaction conditions and high production costs, which limit the application of carbon nanotubes. Chemical vapor deposition refers to a process in which gaseous substances react on the surface of a solid to produce solid deposits. It is a good process for preparing carbon nanotubes at low cost.

[0003] Since the invention of phenolic resin in the early 19th century, plastic products have been used for more than 100 years. While plastics bring convenience to humans, they also cause huge environmental damage. According to incomplete statistics, the global production of waste plastics reached 300 million tons in 2018, and my country's annual production of waste plastics was about 30 million tons. It takes nearly 500 years for plastics to be completely degraded in nature. Therefore, it is imperative to develop technologies for the resource utilization of waste plastics.

[0004] Waste plastics will produce hydrocarbons such as alkanes, alkenes, alkynes, and aromatics when heated and decomposed in a vacuum or inert gas environment. Oxygen-containing plastics will also produce CO, alcohols and other substances. These carbon-containing organic substances can be used as carbon sources for the production of carbon nanotubes by vapor deposition. The preparation of carbon nanotubes by catalytic pyrolysis of waste plastics as raw materials is of great significance to the resource utilization of waste plastics and the low-cost preparation of carbon nanotubes. CN112408364A discloses a method for preparing carbon nanotubes by catalytic pyrolysis of waste thermosetting plastics. The thermosetting plastics are deposited on Fe@NiO core-shell catalysts by two-step reactions using a pyrolysis furnace and a catalytic cracking furnace. However, this process has the problems of long process routes and complex catalyst preparation. CN112320787A discloses a method for preparing nano-carbon materials and its application. Carbon nanotubes are obtained by using polymers such as plastics through three-stage microwave treatment. However, the above method has the problems of complex process routes and difficult microwave power regulation. Summary of the invention

[0005] In view of the problems existing in the prior art, the main purpose of the present invention is to provide a method for preparing carbon nanotubes by catalytic pyrolysis using waste plastics as raw materials and the prepared carbon nanotubes. The method of the present invention does not require multi-step reactions. By preparing a highly dispersed transition metal catalyst, the pyrolysis reaction of the waste plastics and the catalytic modification reaction are coupled in a reactor, and easily functionalized carbon nanotubes can be prepared by a one-step pyrolysis reaction. It has the advantages of simple process and operation and low cost. The graphitization degree and easy oxidation degree of the prepared easily functionalized carbon nanotubes are both within a reasonable range, and they are easily modified by chemical modification to introduce functional groups on their surface to make them functionalized, thereby broadening the application scenarios of carbon nanotubes.

[0006] In order to achieve the above-mentioned object of the present invention, the present invention first provides a carbon nanotube, wherein the functionalization index α of the carbon nanotube is 0.4-0.6, and the functionalization index calculation formula is shown in formula (1):

[0007] Formula (1)

[0008] In formula (1), m 1 is the weight loss percentage of carbon nanotubes at 500-600℃ under thermogravimetric experimental conditions, m 2 is the weight loss percentage of the carbon nanotube when the temperature is 600°C to the weight loss equilibrium under the thermogravimetric experimental conditions, wherein the thermogravimetric experimental conditions are as follows: the heating rate is 5°C / min, the carrier gas is clean air, and the carrier gas flow rate is 20 mL / min; in formula (1), θ is the diffraction angle of the wide-angle diffraction spectrum of the carbon nanotube measured under the X-ray diffractometer, and the X-ray diffraction experimental method is to select Cu target Kα rays, set the emitter voltage and current to 40 kV and 40 mA respectively, and set the X-ray diffraction experiment to 0.1 o / s scanning speed and 0.02 o Continuous scanning is performed with a step size of .

[0009] In order to achieve the above-mentioned object of the present invention, the first and second aspects of the present invention provide a method for preparing carbon nanotubes, comprising the following steps:

[0010] (1) petroleum coke, transition metal precursor, support precursor and activator are uniformly mixed and activated, and then washed and dried to obtain sample A;

[0011] (2) treating the sample A obtained in step (1) in the presence of an oxygen-containing atmosphere to obtain a sample B;

[0012] (3) Under contact conditions, the sample B obtained in step (2) is uniformly mixed with waste plastics and subjected to a pyrolysis reaction to obtain carbon nanotubes.

[0013] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the transition metal precursor in step (1) is a transition metal salt, and the transition metal can be selected from one or more of Fe, Co, and Ni, preferably Fe and / or Ni; the transition metal salt includes but is not limited to one or more of nitrates, sulfates, hydrochlorides, etc., preferably nitrates.

[0014] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the petroleum coke in step (1) is a product obtained by converting heavy oil through a thermal cracking process, and has an irregular black block (or granular) appearance. Specifically, it can be a solid product obtained by delayed coking of catalytic oil slurry.

[0015] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the support precursor in step (1) is an aluminum-containing compound, which may be an aluminum salt and / or aluminate, and specifically may include but is not limited to one or more of aluminum nitrate, aluminum sulfate, aluminum hydrochloride, and aluminate, preferably aluminum nitrate. Furthermore, it may be at least one of aluminum nitrate, aluminum sulfate, aluminum chloride, sodium aluminate, and potassium aluminate.

[0016] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the activator in step (1) can be selected from one or more of potassium hydroxide, sodium hydroxide, potassium bicarbonate, sodium bicarbonate, potassium carbonate, and sodium carbonate, preferably potassium hydroxide.

[0017] Furthermore, in the above-mentioned method for preparing carbon nanotubes, in step (1), the mass ratio of petroleum coke, transition metal precursor (calculated as transition metal element), support precursor (calculated as Al element) and activator is 1:4-16:4-32:0.5-4, preferably 1:6-8:6-16:1-3.

[0018] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the activation process in step (1) is to mix petroleum coke, transition metal precursor, support precursor and activator evenly under the condition of inert atmosphere and heat to activation temperature for activation treatment, wherein the inert atmosphere is one or more of nitrogen, helium, neon and argon; the activation temperature is 400-1000°C, preferably 700-900°C, and the activation time is 5-240min, preferably 20-120min. It is further preferred that the activation process is carried out under microwave radiation, the microwave frequency is 2450MHz or 915MHz; the microwave power is 1-10kw per kg of activated raw material, preferably 2-4kw. When activated under microwave radiation conditions, it is further preferred to include two stages of activation, the first stage of which is activated at 400-600°C for 10-60 min under vacuum conditions, and then an inert gas or nitrogen is introduced to normal pressure under constant temperature conditions, and then the temperature is raised to 700-1000°C for activation for 10-30 min under microwave radiation conditions.

[0019] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the washing in step (1) is water washing, and the specific process is to mix the activated sample with deionized water, mix them evenly, and then perform solid-liquid separation until the pH value of the filtrate is neutral. During the washing process, the solid-liquid mass ratio of the activated sample to the deionized water is 1:5 to 1:30, preferably 1:10 to 1:20.

[0020] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the drying conditions in step (1) are as follows: the drying temperature is 100-200°C, preferably the drying temperature is 120-150°C, the drying time is 2-10 hours, preferably the drying time is 4-8 hours; and further, the drying is preferably carried out under vacuum conditions.

[0021] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the treatment process in step (2) is as follows: the sample A obtained in step (1) is contacted with an oxygen-containing gas for treatment, the treatment temperature is 450°C to 650°C, and the volume concentration of oxygen in the oxygen-containing gas is 10% to 100%, preferably 15% to 80%. The oxygen-containing gas is a mixture of oxygen and a carrier gas, and the carrier gas is one or more of nitrogen, helium, neon, argon, krypton, and xenon. More preferably, the sample A obtained in step (1) is contacted with the oxygen-containing gas for treatment, which includes two stages, wherein the first stage treatment temperature is 450°C to 500°C, and the volume concentration of oxygen in the oxygen-containing gas is 21% to 100%, preferably 50% to 80%; the second stage treatment temperature is 600°C to 650°C; the volume concentration of oxygen in the oxygen-containing gas is 10% to 21%, preferably 15% to 21%.

[0022] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the waste plastic in step (3) can be plastic products from any source, including but not limited to at least one of polyolefin waste plastics and oxygen-containing waste plastics; wherein the polyolefin waste plastics can be at least one of polyethylene, polypropylene, polystyrene and other polyolefin waste plastics, and the oxygen-containing waste plastics can be at least one of polyester plastics.

[0023] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the weight ratio of the sample B obtained in step (2) described in step (3) to the waste plastic is 1:0.5-1, preferably 1:0.5-0.75. Furthermore, in order to ensure that the waste plastic and the sample B are fully mixed, the waste plastic can be crushed before mixing, and the particle size of the waste plastic particles is controlled to be less than 0.5 cm, preferably less than 0.1 cm.

[0024] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the pyrolysis reaction in step (3) is carried out in the presence of an inert atmosphere, and the inert atmosphere is one or more of nitrogen, helium, neon, argon, krypton, and xenon.

[0025] Furthermore, in the above-mentioned method for preparing carbon nanotubes, the pyrolysis reaction temperature in step (3) is 600-800°C, preferably 650-750°C. It is further preferred that the pyrolysis process is carried out under microwave radiation conditions, with a microwave frequency of 2450 MHz or 915 MHz; the sample heating rate under the microwave field is controlled to be 50-500°C / min, preferably 50-100°C / min, and the temperature is kept constant for 10-60 minutes.

[0026] The third aspect of the present invention provides a carbon nanotube obtained by the above preparation method, wherein the functionalization index α of the carbon nanotube is 0.4 to 0.6, and the functionalization index calculation formula is shown in formula (1):

[0027] Formula (1)

[0028] In formula (1), m 1 is the weight loss percentage of carbon nanotubes at 500-600℃ under thermogravimetric experimental conditions, m 2 is the weight loss percentage of the carbon nanotube when the temperature is 600°C to the weight loss equilibrium under the thermogravimetric experimental conditions, wherein the thermogravimetric experimental conditions are as follows: the heating rate is 5°C / min, the carrier gas is clean air, and the carrier gas flow rate is 20 mL / min; in formula (1), θ is the diffraction angle of the wide-angle diffraction spectrum of the carbon nanotube measured under the X-ray diffractometer, and the X-ray diffraction experimental method is to select Cu target Kα rays, set the emitter voltage and current to 40 kV and 40 mA respectively, and set the X-ray diffraction experiment to 0.1 o / s scanning speed and 0.02 o Continuous scanning is performed with a step size of .

[0029] Compared with the prior art, the carbon nanotubes and the preparation method thereof provided by the present invention have the following advantages:

[0030] 1. The carbon nanotubes provided by the present invention are easy to be chemically modified, and different types of functional groups can be easily introduced into the surface of the carbon nanotubes to achieve different functions.

[0031] 2. In the method for preparing carbon nanotubes of the present invention, waste plastic raw materials are used. First, a transition metal precursor and a support precursor are introduced during the activation process of petroleum coke. A catalytic material precursor with highly dispersed active components (transition metals) is obtained by in-situ synthesis. Then, a catalyst with highly dispersed active components is obtained by oxidation treatment. Then, carbon nanotubes are prepared using waste plastic as raw materials. The pyrolysis reaction and catalytic modification reaction of waste plastics are coupled in a reactor. Functionalized carbon nanotubes can be prepared through a one-step pyrolysis reaction, which has the advantages of simple process and low cost. The graphitization degree and oxidation degree of the functionalized carbon nanotubes prepared by the method of the present invention are both within a reasonable range. They are easily modified by chemical modification to introduce functional groups on their surfaces to functionalize them, thereby broadening the application scenarios of carbon nanotubes. The present invention can realize the recycling of waste plastics and the high added value utilization of products. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is an electron microscope photograph (500nm) of the sample prepared in Example 1 of the present invention.

[0033] Figure 2 This is an electron microscope photograph (20 nm) of the sample prepared in Example 1 of the present invention.

[0034] Figure 3 The TG curve of the sample prepared in Example 1 of the present invention.

[0035] Figure 4 The XRD spectrum of the sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and effect of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Thermogravimetric testing was performed on a STA449F5 synchronous thermal analyzer from NETZSCH. First, about 10 mg of sample was weighed and added to an alumina crucible. The carrier gas (clean air) flow rate was adjusted to 20 mL / min, and the temperature was raised to the set temperature at a heating rate of 5°C / min. The weight loss curve was recorded, and then the temperature was cooled to room temperature (25°C). m 1 It is the weight loss percentage of carbon nanotube products under thermogravimetric test conditions at 500-600℃. m 2 It is the weight loss percentage of the carbon nanotube product when the temperature is 600°C to the weight loss equilibrium under the thermogravimetric experimental conditions. The thermogravimetric experimental conditions are a heating rate of 5°C / min, clean air as the carrier gas, and a carrier gas flow rate of 20mL / min.

[0038] XRD test was carried out using Japan Ricoh D / max -3 The X-ray diffractometer of type C was used. The sample was a powdered sample, placed on a slide coated with Canada resin, and then pressed into a film. The operating conditions were Cu target Kα radiation, the emitter voltage and current were set to 40kV and 40mA respectively, and the o / s scanning speed and 0.02 o The scanning range is 10 o to 70 o .

[0039] Example 1

[0040] 10g petroleum coke, 433g Fe(NO 3 ) 3 9H 2 O、833gAl(NO 3 ) 3 9H 2 O, 30gKOH were mixed evenly, and then activated in a microwave field, the microwave power was controlled to be 5.2kw, first the activation chamber was evacuated, the activation chamber temperature was controlled to rise from room temperature to 500℃, and the temperature was kept constant for 30min, then the temperature was kept constant, nitrogen was flushed into the activation chamber until normal pressure, and then the activation chamber temperature was raised to 900℃ under microwave radiation conditions, and the temperature was kept constant for 20min. The activated sample was fully stirred and mixed with deionized water at a mass ratio of 1:10, and then filtered to separate the solid and liquid, and repeated several times until the pH of the filtrate was 7. The washed sample was placed in a vacuum drying oven and kept at 150℃ for 8h to obtain sample A. The dried sample A was placed in a muffle furnace, a mixed gas of 80% oxygen and 20% nitrogen was introduced, and the temperature was raised from room temperature to 450℃, and the temperature was kept constant for 30min; then the atmosphere was switched to a mixed gas of 21% oxygen and 79% nitrogen, the temperature was raised from 450℃ to 600℃, and the temperature was kept constant for 30min; finally, it was naturally cooled to room temperature to obtain sample B. The polyethylene waste plastic was crushed to a particle size of less than 0.1 cm, and then the obtained sample B was mixed with the waste plastic in a mass ratio of 1:0.5 and placed in a microwave field. The heating rate was set to 50℃ / min, the final pyrolysis temperature was 650℃, and the temperature was kept constant for 30 minutes to obtain carbon nanotubes. After the reaction, the carbon nanotubes obtained had a good morphology and a relatively uniform diameter. The outer diameter was mainly distributed between 12 and 20 nm, the wall thickness was distributed between 4 and 6 nm, and the number of tube wall layers was distributed between 6 and 11. Under the conditions of a heating rate of 5℃ / min, clean air as the carrier gas, and a carrier gas flow rate of 20mL / min, the weight loss percentage at 500-600℃ was 22.30%, and the weight loss percentage at 600℃ to the weight loss equilibrium was 11.04%. The XRD results showed that the diffraction angle θ=12.9 oThe functionalization index α of the sample was calculated to be 0.45.

[0041] Example 2

[0042] 10g petroleum coke, 281g Fe(NO 3 ) 3 9H 2 O. 202g Ni(NO 3 ) 2 6H 2 O、2222gAl(NO 3 ) 3 , 30gKOH were mixed evenly, and then activated under a microwave field. The microwave power was controlled to be 5.4 kw. First, the activation chamber was evacuated, and the temperature of the activation chamber was controlled to rise from room temperature to 600°C, and the temperature was kept constant for 20 minutes. Then, the temperature was kept constant, and nitrogen was flushed into the activation chamber until it reached normal pressure. Then, the temperature of the activation chamber was raised to 1000°C under microwave radiation conditions, and the temperature was kept constant for 10 minutes. The activated sample was fully stirred and mixed with deionized water in a mass ratio of 1:20, and then filtered to separate the solid and liquid. Repeat several times until the pH of the filtrate is 7. The washed sample was placed in a vacuum drying oven and kept at 150°C for 8 hours to obtain sample A. The dried sample A was placed in a muffle furnace, a mixture of 50% oxygen and 50% nitrogen was introduced, and the temperature was raised from room temperature to 500°C and kept constant for 30 minutes; then the atmosphere was switched to a mixture of 15% oxygen and 85% nitrogen, the temperature was raised from 500°C to 650°C, and the temperature was kept constant for 30 minutes; finally, it was naturally cooled to room temperature to obtain sample B. The polypropylene waste plastic was crushed to a particle size less than 0.1 cm, and the sample B obtained in the previous step was mixed with the waste plastic in a mass ratio of 1:0.75 and placed in a microwave field, the heating rate was set to 100°C / min, the pyrolysis final temperature was 650°C, and the temperature was kept constant for 30 minutes to obtain carbon nanotubes. After the reaction, the carbon nanotubes obtained had good morphology and relatively uniform diameter. The outer diameter was mainly distributed between 16 and 30 nm, the wall thickness was distributed between 7 and 10 nm, and the number of tube wall layers was distributed between 17 and 25. Under the conditions of the thermogravimetric experiment with a heating rate of 5°C / min, clean air as the carrier gas, and a carrier gas flow rate of 20 mL / min, the weight loss percentage at 500-600°C was 28.85%, and the weight loss percentage at 600°C when the weight loss reached equilibrium was 12.34%. The XRD results showed that the diffraction angle θ=12.8 o The functionalization index α of the sample was calculated to be 0.52.

[0043] Example 3

[0044] 10g petroleum coke, 193g Fe 2 (SO 4 ) 3 、149g NiSO 4、1392gAl 2 (SO 4 ) 3 , 30g KHCO 3 Mix evenly, and then activate under microwave field. Control microwave power to 7.1 kw. First, evacuate the activation chamber, control the activation chamber temperature from room temperature to 400℃, keep constant temperature for 60min, then keep constant temperature, flush nitrogen into the activation chamber until normal pressure, and then keep microwave radiation to raise the activation chamber temperature to 700℃, keep constant temperature for 30min. Stir and mix the activated sample with deionized water at a mass ratio of 1:15, and then filter to separate the solid and liquid, repeat several times until the filtrate pH is 7. Put the washed sample into a vacuum drying oven, keep constant temperature at 150℃ for 4h to obtain sample A. Place the dried sample A in a muffle furnace, pass a mixture of 21% oxygen and 79% nitrogen, and heat from room temperature to 475℃, keep constant temperature for 30min; then switch the atmosphere to a mixture of 18% oxygen and 82% nitrogen, raise the temperature from 475℃ to 625℃, keep constant temperature for 30min; finally cool naturally to room temperature to obtain sample B. Mix polypropylene and polystyrene waste plastics in a mass ratio of 1:1, crush them to a particle size of less than 0.1cm, mix the sample B obtained in the previous step with the mixed waste plastics in a mass ratio of 1:0.6 and place them in a microwave field, set the heating rate to 80℃ / min, the pyrolysis final temperature to 750℃, and keep the temperature constant for 10min to obtain carbon nanotubes. Under the conditions of a heating rate of 5℃ / min, clean air as the carrier gas, and a carrier gas flow rate of 20mL / min, the weight loss percentage at 500-600℃ was 25.66%, and the weight loss percentage at 600℃ to the equilibrium was 12.20%. The XRD results showed that the diffraction angle θ=12.7 o The functionalization index α of the sample was calculated to be 0.46.

[0045] Example 4

[0046] 10g petroleum coke, 331g Fe(NO 3 ) 3 9H 2 O、119gCo(NO 3 ) 2 6H 2 O, 541gAlCl 3 , 20gK 2 CO 3Mix evenly, and then activate under microwave field. Control microwave power to 3kw. First, evacuate the activation chamber, control the activation chamber temperature from room temperature to 500℃, keep constant temperature for 30min, then keep constant temperature, flush nitrogen into the activation chamber until normal pressure, and then keep microwave radiation to raise the activation chamber temperature to 850℃, keep constant temperature for 15min. The activated sample is fully stirred and mixed with deionized water at a mass ratio of 1:20, and then filtered to separate the solid and liquid, and repeated several times until the filtrate pH is 7. The washed sample is placed in a vacuum drying oven, and sample A is obtained after constant temperature at 120℃ for 8h. The dried sample A is placed in a muffle furnace, a mixture of 50% oxygen and 50% nitrogen is introduced, and the temperature is raised from room temperature to 500℃, and the temperature is kept constant for 30min; then the atmosphere is switched to a mixture of 15% oxygen and 85% nitrogen, the temperature is raised from 500℃ to 600℃, and the temperature is kept constant for 30min; finally, it is naturally cooled to room temperature to obtain sample B. Polyethylene waste plastic, polypropylene waste plastic, polyester waste plastic were mixed in a mass ratio of 1:1:1, crushed to a particle size of less than 0.1 cm, and the sample B obtained in the previous step was mixed with the mixed waste plastic in a mass ratio of 1:0.5 and placed in a microwave field, and the heating rate was set to 100℃ / min, the pyrolysis final temperature was 700℃, and the temperature was kept constant for 60min to obtain carbon nanotubes. Under the conditions of a heating rate of 5℃ / min, clean air as carrier gas, and a carrier gas flow rate of 20mL / min, the weight loss percentage at 500-600℃ was 28.10%, and the weight loss percentage at 600℃ to the weight loss equilibrium was 10.97%. The XRD results showed that the diffraction angle θ=12.8 o The functionalization index α of the sample was calculated to be 0.57.

[0047] Example 5

[0048] 10g petroleum coke, 211g Fe(NO 3 ) 3 9H 2 O, 76g Co(NO 3 ) 2 6H 2 O, 76g Ni(NO 3 ) 2 6H 2 O, 334gNaAlO 2, 10gNaOH mixed evenly, and then activated under microwave field. Control microwave power to 2.8 kw. First, evacuate the activation chamber, control the activation chamber temperature from room temperature to 500℃, keep constant temperature for 30min, then keep constant temperature, flush nitrogen into the activation chamber until normal pressure, and then keep microwave radiation conditions to raise the activation chamber temperature to 900℃, keep constant temperature for 20min. The activated sample is fully stirred and mixed with deionized water at a mass ratio of 1:10, and then filtered to separate the solid and liquid, and repeated several times until the filtrate pH is 7. The washed sample is placed in a vacuum drying oven, and sample A is obtained after constant temperature at 120℃ for 8h. The dried sample A is placed in a muffle furnace, pure oxygen is introduced, and the temperature is raised from room temperature to 450℃, and the temperature is kept constant for 30min; then the atmosphere is switched to a mixture of 21% oxygen and 79% nitrogen, the temperature is raised from 450℃ to 600℃, and the temperature is kept constant for 30min; finally, it is naturally cooled to room temperature to obtain sample B. The polyethylene waste plastic was crushed to a particle size of less than 0.1 cm, and the sample B obtained in the previous step was mixed with the waste plastic at a mass ratio of 1:0.5 and placed in a microwave field. The heating rate was set to 50℃ / min, the pyrolysis final temperature was 650℃, and the temperature was kept constant for 30min to obtain carbon nanotubes. Under the conditions of a heating rate of 5℃ / min, clean air as the carrier gas, and a carrier gas flow rate of 20mL / min, the weight loss percentage at 500-600℃ was 26.35%, and the weight loss percentage at 600℃ to the weight loss equilibrium was 13.88%. The XRD results showed that the diffraction angle θ=12.6 o The functionalization index α of the sample was calculated to be 0.41.

[0049] Comparative Example 1

[0050] 10g petroleum coke, 433g Fe(NO 3 ) 3 9H 2O, 30g KOH were mixed evenly, and then activated under a microwave field, the microwave power was controlled to be 1.4kw, first the activation chamber was evacuated, the activation chamber temperature was controlled to rise from room temperature to 500℃, and the temperature was kept constant for 30min, then the temperature was kept constant, nitrogen was flushed into the activation chamber until normal pressure, and then the activation chamber temperature was raised to 900℃ under microwave radiation conditions, and the temperature was kept constant for 20min. The activated sample was fully stirred and mixed with deionized water at a mass ratio of 1:10, and then filtered to separate the solid and liquid, and repeated several times until the pH of the filtrate was 7. The washed sample was placed in a vacuum drying oven and kept at 150℃ for 8h to obtain sample A. The dried sample A was placed in a muffle furnace, a mixture of 80% oxygen and 20% nitrogen was introduced, and the temperature was raised from room temperature to 450℃, and the temperature was kept constant for 30min; then the atmosphere was switched to a mixture of 21% oxygen and 79% nitrogen, the temperature was raised from 450℃ to 600℃, and the temperature was kept constant for 30min; finally, it was naturally cooled to room temperature to obtain sample B. The polyethylene waste plastic was crushed to a particle size less than 0.1 cm, and then the obtained sample B was evenly mixed with the waste plastic in a mass ratio of 1:0.5 and placed in a microwave field. The heating rate was set to 50°C / min, the final pyrolysis temperature was 650°C, and the temperature was kept constant for 30 minutes. No carbon nanotubes were obtained in the reaction.

[0051] Comparative Example 2

[0052] With Fe(NO 3 ) 3 9H 2 O is the active component precursor, and the catalyst with the carrier as activated alumina, the active component as Fe, and the active component loading as 30wt% is prepared by equal volume impregnation method. The drying condition is 150℃, and the drying time is 6h. The dried sample is placed in a muffle furnace, and a mixture of 80% oxygen and 20% nitrogen is introduced, and the temperature is raised from room temperature to 450℃, and the temperature is kept constant for 30min; then the atmosphere is switched to a mixture of 21% oxygen and 79% nitrogen, and the temperature is raised from 450℃ to 600℃, and the temperature is kept constant for 30min; finally, it is naturally cooled to room temperature to obtain the catalyst. Polyethylene waste plastics are crushed to a particle size of less than 0.1cm, and then the obtained catalyst is mixed with waste plastics in a mass ratio of 1:0.5 and placed in a microwave field, and the heating rate is set to 50℃ / min, the pyrolysis final temperature is 650℃, and the temperature is kept constant for 30min, but no carbon nanotubes are obtained.

Claims

1. A method for preparing carbon nanotubes, comprising the following steps: (1) petroleum coke, transition metal precursor, support precursor and activator are mixed evenly and then activated, and then washed and dried to obtain sample A; the support precursor is an aluminum-containing compound, and the aluminum-containing compound is an aluminum salt and / or aluminate; the activator is selected from one or more of potassium hydroxide, sodium hydroxide, potassium bicarbonate, sodium bicarbonate, potassium carbonate and sodium carbonate; (2) treating the sample A obtained in step (1) in the presence of an oxygen-containing atmosphere to obtain a sample B; (3) Under contact conditions, the sample B obtained in step (2) is uniformly mixed with waste plastics and subjected to a pyrolysis reaction to obtain carbon nanotubes.

2. The method for preparing carbon nanotubes according to claim 1, characterized in that: In step (1), the transition metal precursor is a transition metal salt, and the transition metal is selected from one or more of Fe, Co, and Ni; the transition metal salt includes but is not limited to one or more of nitrates, sulfates, and hydrochlorides.

3. The method for preparing carbon nanotubes according to claim 2, characterized in that: The transition metal is Fe and / or Ni.

4. The method for preparing carbon nanotubes according to claim 1, characterized in that: In step (1), the support precursor is one or more of aluminum nitrate, aluminum sulfate, aluminum hydrochloride, and aluminum metaaluminate.

5. The method for preparing carbon nanotubes according to claim 1, characterized in that: In step (1), the support precursor is at least one of aluminum nitrate, aluminum sulfate, aluminum chloride, sodium aluminate, and potassium aluminate.

6. The method for preparing carbon nanotubes according to claim 1, characterized in that: In step (1), the mass ratio of petroleum coke, transition metal precursor calculated as transition metal element, support precursor calculated as Al element and activator is 1:4-16:4-32:0.5-4.

7. The method for preparing carbon nanotubes according to claim 1, characterized in that: In step (1), the mass ratio of petroleum coke, transition metal precursor calculated as transition metal element, support precursor calculated as Al element and activator is 1:6-8:6-16:1-3.

8. The method for preparing carbon nanotubes according to claim 1, characterized in that: The activation process in step (1) is to mix the petroleum coke, transition metal precursor, support precursor and activator evenly under the condition of inert atmosphere and heat them to activation temperature for activation treatment, wherein the inert atmosphere is one or more of nitrogen, helium, neon and argon; the activation temperature is 400-1000°C and the activation time is 5-240min.

9. The method for preparing carbon nanotubes according to claim 8, characterized in that: The activation temperature is 700-900°C, and the activation time is 20-120 minutes.

10. The method for preparing carbon nanotubes according to claim 8, characterized in that: The activation process is carried out under microwave radiation conditions, the microwave frequency is 2450MHz or 915MHz; the microwave power is 1-10kw per kg of activated raw material.

11. The method for preparing carbon nanotubes according to claim 8, characterized in that: The activation process is carried out under microwave radiation conditions, the microwave frequency is 2450MHz or 915MHz; the microwave power is 2-4kw per kg of activated raw material.

12. The method for preparing carbon nanotubes according to claim 10 or 11, characterized in that: When activated under microwave radiation conditions, it includes two stages of activation. The first stage is activated at 400-600°C for 10-60 minutes under vacuum conditions. Under constant temperature conditions, inert gas or nitrogen is introduced to normal pressure, and the temperature is continued to be raised to 700-1000°C for activation for 10-30 minutes under microwave radiation conditions.

13. The method for preparing carbon nanotubes according to claim 1, characterized in that: The drying conditions in step (1) are as follows: the drying temperature is 100 to 200° C., and the drying time is 2 to 10 hours.

14. The method for preparing carbon nanotubes according to claim 1, characterized in that: The treatment process in step (2) is as follows: the sample A obtained in step (1) is contacted with an oxygen-containing gas for treatment, the treatment temperature is 450° C. to 650° C., and the volume concentration of oxygen in the oxygen-containing gas is 10% to 100%; the oxygen-containing gas is a mixture of oxygen and a carrier gas, and the carrier gas is one or more of nitrogen, helium, neon, argon, krypton, and xenon.

15. The method for preparing carbon nanotubes according to claim 1, characterized in that: The treatment process in step (2) is as follows: the sample A obtained in step (1) is contacted with an oxygen-containing gas for treatment, the treatment temperature is 450° C. to 650° C., and the volume concentration of oxygen in the oxygen-containing gas is 15% to 80%; the oxygen-containing gas is a mixture of oxygen and a carrier gas, and the carrier gas is one or more of nitrogen, helium, neon, argon, krypton, and xenon.

16. The method for preparing carbon nanotubes according to claim 14 or 15, characterized in that: The sample A obtained in step (1) is contacted with the oxygen-containing gas for treatment, which includes two stages, wherein the first stage treatment temperature is 450°C to 500°C, and the oxygen volume concentration in the oxygen-containing gas is 21% to 100%; the second stage treatment temperature is 600°C to 650°C; the oxygen volume concentration in the oxygen-containing gas is 10% to 21%.

17. The method for preparing carbon nanotubes according to claim 14 or 15, characterized in that: The sample A obtained in step (1) is contacted with the oxygen-containing gas for treatment, which includes two stages, wherein the treatment temperature of the first stage is 450°C to 500°C, and the oxygen volume concentration in the oxygen-containing gas is 50 to 80%; the treatment temperature of the second stage is 600°C to 650°C; the oxygen volume concentration in the oxygen-containing gas is 15 to 21%.

18. The method for preparing carbon nanotubes according to claim 1, characterized in that: The waste plastics in step (3) are plastic products from any source, including but not limited to at least one of polyolefin waste plastics and oxygen-containing waste plastics; wherein the polyolefin waste plastics are at least one of polyethylene, polypropylene, and polystyrene waste plastics, and the oxygen-containing waste plastics are at least one of polyester plastics.

19. The method for preparing carbon nanotubes according to claim 1, characterized in that: The weight ratio of the sample B obtained in step (2) described in step (3) to the waste plastic is 1:0.5-1.

20. The method for preparing carbon nanotubes according to claim 1, characterized in that: The weight ratio of the sample B obtained in step (2) described in step (3) to the waste plastic is 1:0.5-0.

75.

21. The method for preparing carbon nanotubes according to claim 19 or 20, characterized in that: The waste plastics were crushed before being mixed with sample B to control the particle size of the waste plastics to be less than 0.5 cm.

22. The method for preparing carbon nanotubes according to claim 19 or 20, characterized in that: The waste plastics were crushed before being mixed with sample B, and the particle size of the waste plastic particles was controlled to be less than 0.1 cm.

23. The method for preparing carbon nanotubes according to claim 1, characterized in that: The pyrolysis reaction in step (3) is carried out in the presence of an inert atmosphere, wherein the inert atmosphere is one or more of nitrogen, helium, neon, argon, krypton, and xenon.

24. The method for preparing carbon nanotubes according to claim 1, characterized in that: The pyrolysis reaction temperature in step (3) is 600-800°C.

25. The method for preparing carbon nanotubes according to claim 1, characterized in that: The pyrolysis reaction temperature in step (3) is 650-750°C.

26. The method for preparing carbon nanotubes according to claim 24 or 25, characterized in that: The pyrolysis process is carried out under microwave radiation conditions, and the microwave frequency is 2450MHz or 915MHz; the sample heating rate under the microwave field is controlled to be 50-500℃ / min, and the constant temperature is maintained for 10-60min.

27. A carbon nanotube obtained by the preparation method according to any one of claims 1 to 26.

28. The carbon nanotube according to claim 27, characterized in that: The functionalization index α of the carbon nanotube is 0.4 to 0.6, and the functionalization index calculation formula is shown in formula (1): Formula (1) In formula (1), m 1 is the weight loss percentage of carbon nanotubes at 500-600℃ under thermogravimetric experimental conditions, m 2 is the weight loss percentage of the carbon nanotube when the weight loss reaches equilibrium at 600°C under the thermogravimetric experimental conditions, wherein the thermogravimetric experimental conditions are as follows: the heating rate is 5°C / min, the carrier gas is clean air, and the carrier gas flow rate is 20 mL / min; in formula (1), q is the diffraction angle of the wide-angle diffraction spectrum of the carbon nanotube measured under an X-ray diffractometer, and the X-ray diffraction experimental method is to select Cu target Kα rays, set the emitter voltage and current to 40 kV and 40 mA respectively, and set the X-ray diffraction experiment to 0.1 o / s scanning speed and 0.02 o Continuous scanning is performed with a step size of .

Citation Information

Patent Citations

  • Preparation method and application of nano carbon material

    CN112320787A

  • Method for preparing carbon nanometer tubes through waste plastic catalytic pyrolysis by two-section process

    CN107934938A

  • Method for preparing carbon nanotubes by catalytic pyrolysis of waste thermosetting plastics

    CN112408364A